Understanding policy and programming on sex-selection in Tamil Nadu: Ethnographic and sociological reflections - Shahid Perwez (University of Bath, Centre for Development Studies (CDS), 2013)
The family-planning programme of Tamil Nadu, largely a female sterilisation campaign, has been applauded as one of the successful public health interventions in India, which had arguably led to the drastic fertility decline in the state. To the state's dismay, however, the fertility decline in Tamil Nadu was also attended by the increasing reports of female infanticide and sex-selective abortion. In its subsequent response, the state in Tamil Nadu introduced specific policy and interventionary measures to curb the practice. In this paper, I critically examine these responses in their local ethnographic contexts to highlight the manner in which family-planning goals get intertwined with the political intervention on the issue of sex-selection. This leads to women's diminishing access to unmet needs for family planning and reproductive health services thereby contributing to further marginalisation of Tamil women.
Keywords: 330; Sex-selection; female infanticide; son preference; family-planning; policy and schemes; women and girl children; Tamil Nadu; India; South Asia